2004
DOI: 10.1021/jp035361q
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on Photoluminescence of Highly Luminescent CdSe and CdSe/ZnS Core/Shell Nanocrystals in Polymer Thin Films

Abstract: We report our systematic studies of the environmental effects on the photoluminescence (PL) from colloidal CdSe nanocrystals (NCs) embedded in polymer thin films. The highly luminescent bare-core CdSe NCs were significantly more robust than the core/shell CdSe/ZnS NCs against photoannealing under inert environments, while the core/shell NCs are more resistant to photooxidation. For the case of bare-core NCs, we show the importance of the initial photoactivation as the proper treatment for subsequent studies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(199 citation statements)
references
References 36 publications
6
193
0
Order By: Relevance
“…The suited PL properties include broad absorption band, size tuneable spectral emission, higher photostability, and emission lifetime ranging between several hundreds of picosecond and tens of nanosecond [6]. In the last ten years, authors reported the sensitivity of colloidal QDs embedded into polymeric matrix [7][8][9][10][11], sol-gel materials [12,13] or dispersed in Al 2 O 3 nanopore array [13]. Per se they display sensitivity towards some commonly used solvents like methanol, ethanol, acetone and chloroform [12].…”
Section: Introductionmentioning
confidence: 99%
“…The suited PL properties include broad absorption band, size tuneable spectral emission, higher photostability, and emission lifetime ranging between several hundreds of picosecond and tens of nanosecond [6]. In the last ten years, authors reported the sensitivity of colloidal QDs embedded into polymeric matrix [7][8][9][10][11], sol-gel materials [12,13] or dispersed in Al 2 O 3 nanopore array [13]. Per se they display sensitivity towards some commonly used solvents like methanol, ethanol, acetone and chloroform [12].…”
Section: Introductionmentioning
confidence: 99%
“…28 While higher laser intensities accelerate the process of blueing, 32 slow spectral blue shifts have also been observed under low-level illumination from a Xe arc lamp (≈3 W cm -2 ). 26 From our analysis of approximately 200 measured fluorescence time traces of individual photooxidized quantum dots, we deduced that the duration of the off periods remains unaffected by the blueing process ( Figure 3).…”
mentioning
confidence: 99%
“…Accordingly, the fluorescence intensity of QDs may increase in the presence of a Lewis base and a decrease in the presence of a Lewis acid. [34][35][36] The observed quenching of fluorescence intensity of EDA-CDs in the presence of GSH may be due to the Lewis acid nature of the thiol group in GSH. The hydrophilic thiols decrease the fluorescence intensity by replacing the amine species from the surface of the QDs.…”
Section: Fluorescence Quenching Of Cds By Gshmentioning
confidence: 99%